Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations HINTS FOR THE BUSY HOUSEWIFE allowed to stand a short time before washing. Soda should never be used for aluminium pans or utensils; any stains may be removed with a little lemon, or by boiling acid fruit, such as rhubarb, green gooseberries, or apples in the pan. Baking Tins and Pie Dishes. — Wash in hot soapy water. If burnt, apply salt on a damp cloth. If badly burnt use a good, smooth-cleaning powder cleanser sprinkled on a damp cloth. For very greasy tins, add a little soda to the washing water. Children’s Feeding Bottles. — Bottles and teats should be scalded once daily. After feeds both should be rinsed in cold water, the teats rubbed on both sides with common salt, rinsed, left to drain in a saucer and covered with a teacup. A SOAPY HINT OR TWO Odd Scraps of Soap. — A good-sized slab of soap is always easiest to use for washing-days, and for washing floors, etc. Don’t be afraid to use a new bar of soap. There are lots of odd ways of using up the small pieces. A Soap-Saver. — Get a tin box (a cocoa tin does excellently), and with a sharp nail and a hammer knock little holes in the bottom and up the sides. Then fill the tin with scraps of soap. When you wish to obtain a good lather, swish the tin about in the water for a few seconds. You’ll be surprised at the result. For Washing-up. — Tiny scraps of soap, if dried in a cool oven, can be grated, and make a useful soap-powder for washing-up instead of using soda, which dries up the natural oils of the skin. Page Thirteen 177/5/8/1